2013
DOI: 10.1016/j.ejvs.2013.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stentgraft Model on Aneurysm Shrinkage in 1,450 Endovascular Aortic Repairs

Abstract: Aneurysm diameter shrinkage can be achieved in most current EVARs with persisting effect at 10 years from repair and indicates the benefit and safety of treatment. Last generation devices seem to be important factors in inducing aneurysm sac shrinkage with similar clinically relevant effects among single models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 22 publications
1
35
2
Order By: Relevance
“…This was also confirmed in our study, where the median survival time of patients with aneurysm shrinkage >5 mm was 8 months longer (P < .0001). In contrast to our study, Cieri et al 15 found lower but still comparable rates of aneurysm shrinkage of 40% (33 of 83 patients) in the Endurant group. However, their study did not report the exact follow-up time in patients receiving this specific device.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This was also confirmed in our study, where the median survival time of patients with aneurysm shrinkage >5 mm was 8 months longer (P < .0001). In contrast to our study, Cieri et al 15 found lower but still comparable rates of aneurysm shrinkage of 40% (33 of 83 patients) in the Endurant group. However, their study did not report the exact follow-up time in patients receiving this specific device.…”
Section: Discussioncontrasting
confidence: 99%
“…Currently, Cieri et al 15 In our analysis, implantation against IFU or peripheral vascular disease could not be identified as risk factors for limb occlusion. Our hypothesis for this complication is that the distal end of the iliac limbs is not always in an optimal apposition to the vessel wall of a tortuous or heavily calcified iliac artery, causing a form of high-grade stenosis or local vessel damage with intimal hyperplasia.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The importance of sac shrinkage has been investigated previously, and contraction of the aneurysm sac has been suggested as a marker for success after EVAR. In a recent publication involving 1450 procedures, Cieri and colleagues reported that persistent shrinkage of the AAA sac (over 5 mm) was associated with rates of freedom from AAA‐related death at 3 and 10 years of 100 and 99·7 per cent respectively. Houbballah and co‐workers reported no postimplant ruptures or conversions, and very low rates of type I leak (2·2 per cent) and secondary intervention (3·3 per cent) at a mean follow‐up of 4·2 years, for patients with significant sac contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Devices were defined as "new generation" if introduced after 2004 and currently in use. 5 After EVAR, patients were scheduled for serial followup imaging with duplex ultrasound and computed tomography angiography (CTA) scan at 1 month, 6 months, and yearly thereafter. Postoperative surveillance was performed using multiphasic CTA with 3-mm cuts, including imaging before the administration of contrast material, after the intravenous administration of contrast material in the arterial phase (arterial phase), and in postcontrast delayed phase (venous phase).…”
Section: Methodsmentioning
confidence: 99%